Multimodal Brain Image Analysis Third International Workshop, MBIA 2013, Held in Conjunction with MICCAI 2013, Nagoya, Japan, September 22, 2013, Proceedings - Shen, Li.; Liu, Tianming; Yap, Pew-Thian.; Huang, Heng.; Shen, Dinggang; Westin, Carl-Fredrik.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the Third International Workshop on Multimodal Brain Image Analysis, MBIA 2013, held in Nagoya, Japan, on September 22, 2013 in conjunction with the 16th International Conference on Medical Image Computing and Computer Assisted Intervention, MICCAI. The 24 revised full papers presented were carefully reviewed and selected from 35 submissions. The papers are organized in topical sections on analysis, methodologies, algorithms, software systems, validation approaches, benchmark datasets, neuroscience and clinical applications.
Analysis -- Methodologies -- Algorithms -- Software systems -- Validation approaches -- Benchmark datasets -- Neuroscience -- Clinical applications.
Keywords: Computer science; Radiology, Medical; Computer software; Artificial intelligence; Computer graphics; Computer vision; Optical pattern recognition; Computer Science; Pattern Recognition; Image Processing and Computer Vision; Computer Graphics; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity; Imaging / Radiology